Changes and relationship of somatosensory cortical electrical activity and hind paw defensive reflex in rats under various anesthetics - Mikite, Katalin; Merész, Nóra; Papp, András (Acta Biologica Szegediensis, 2013)
The effect of four common anesthetics on the spontaneous and evoked activity of the somatosensory cortex and on hind paw withdrawal reflex was studied in rats in acute preparation. The aim was to determine to what extent the choice of anesthetic and the depth of anesthesia may interfere with the effects of agents tested in such a system. Electrical activity was recorded on the dura surface after opening the skull, from the primary projection area of the whiskers which were stimulated electrically. Defensive reflex was elicited by manually pinching the toes of the left hind paw. Anesthesia was initiated with chloral hydrate or ketamine-xylazine, and continued with urethane or thiopental and then urethane. In the spontaneous cortical activity, delta band power was in strong correlation with the depth of anesthesia. Anesthesia also had a clear effect on the amplitude, but not on the latency, of the somatosensory evoked potential. Under effect of chloral hydrate the shape of the evoked potential was different from that seen under ketamine-xylazine or urethane. The results showed that properly chosen electrophysiological parameters can reliably indicate the depth of anesthesia, and that choice of anesthetic and level of anesthesia may effectively interfere with the effects of tested substances.